Green innovation in environmental complexity: The implication of open innovation - Ieva Meidute-Kavaliauskiene; Şemsettin Çiğdem; Aidas Vasilis Vasiliauskas; Bülent Yıldız (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
People have become more conscientious about the environment in recent years. Increasing environmental awareness drives customers to be more selective about environmentally friendly products and forces governments to adopt environmentally friendly policies. As a result, competition in the market becomes more challenging. Thus, companies cannot remain indifferent to adopting environmentally friendly strategies to be sustainable. In this regard, this study investigates the effect of green innovation on firm performance. We also examined whether the environmental uncertainty moderates the investigated effect. For this purpose, first, data were collected from the first 1000 exporting firms declared in 2019 by the Turkey Exporters Assembly using a survey method. Secondly, factor analyses and regression analyses were performed with the data set obtained from 136 companies. As a result of the analysis, it was determined that green innovation increases both environmental performance and economic performance. It also was found that green innovation positively affects firm performance, but environmental uncertainty reduces this effect. According to these results, it was offered that firms should increase their green innovation activities to achieve better outputs and seek ways to reduce environmental uncertainty to keep these outputs at the maximum level. Finally, the research includes some considerations on the positive implications and potential of green innovation in an open-innovation context.
Keywords: 650; environmental performance; environmental uncertainty; green innovation